Determination of Junior High School Location Through Geographic Information System Utilization - Badriyah, Opilona (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Geographic Information Systems (GIS) is a management tool in the form of computer-assisted information related to the system's mapping and analysis of all occurences on earth. In education, GIS can be used to determine the location of the new school. The purpose of writing this article is to explain the importance of GIS in determining the location of education. The object of study is the equity and expansion of education access, in the form of determining the location of new schools. The method of writing this article was using the relevant literature analysis. Conclusion of this article is for equity and justice of public access in obtaining education service, determination of new school location needs to use Geographic Information System.